(untitled) (International Journal of Engineering and Computer Science, 2023)
An exponential growth has observed of network or internet users due to diverse resource and information sharing services. Contrary, network uses also increased in different kinds of attacks. Means network is vulnerable for many types of attacks. Computer network may exploit in different contexts such as denial of service, ping death, malfunction routing, flooding, man in the middle and spoofing attack. Among of these MAC spoofing is kind of attack spoofing attack that target to MAC or physical address of the network host or router. It tampers original address to any other random or user defined address. The aim of the study is to present MAC address and its types. With this, MAC spoofing attack also presented. Implementation environment and method for the MAC spoofing also presented. MAC spoofing is implemented in the KALI Linux operating system with the help of MACCHANGER tool.